CD16‐158‐valine chimeric receptor T cells overcome the resistance of KRAS‐mutated colorectal carcinoma cells to cetuximab. Issue 9 (30th August 2019) - Arriga, Roberto; Caratelli, Sara; Lanzilli, Giulia; Ottaviani, Alessio; Cenciarelli, Carlo; Sconocchia, Tommaso; Spagnoli, Giulio C.; Iezzi, Giandomenica; Roselli, Mario; Lauro, Davide; Coppola, Andrea; Dotti, Gianpietro; et al.
Abstract : KRAS mutations hinder therapeutic efficacy of epidermal growth factor receptor (EGFR)‐specific monoclonal antibodies cetuximab and panitumumab‐based immunotherapy of EGFR+ cancers. Although cetuximab inhibits KRAS‐mutated cancer cell growth in vitro by natural killer (NK) cell‐mediated antibody‐dependent cellular cytotoxicity (ADCC), KRAS‐mutated colorectal carcinoma (CRC) cells escape NK cell immunosurveillance in vivo . To overcome this limitation, we used cetuximab and panitumumab to redirect Fcγ chimeric receptor (CR) T cells against KRAS‐mutated HCT116 colorectal cancer (CRC) cells. We compared four polymorphic Fcγ‐CR constructs including CD16 158F ‐CR, CD16 158V ‐CR, CD32 131H ‐CR, and CD32 131R ‐CR transduced into T cells by retroviral vectors. Percentages of transduced T cells expressing CD32 131H ‐CR (83.5 ± 9.5) and CD32 131R ‐CR (77.7 ± 13.2) were significantly higher than those expressing with CD16 158F ‐CR (30.3 ± 10.2) and CD16 158V ‐CR (51.7 ± 13.7) ( p < 0.003). CD32 131R ‐CR T cells specifically bound soluble cetuximab and panitumumab. However, only CD16 158V ‐CR T cells released high levels of interferon gamma (IFNγ = 1, 145.5 pg/ml ±16.5 pg/ml, p < 0.001) and tumor necrosis factor alpha (TNFα = 614 pg/ml ± 21 pg/ml, p < 0.001) upon incubation with cetuximab‐opsonized HCT116 cells. Moreover, only CD16 158V ‐CR T cells combined with cetuximab killed HCT116 cells and A549 KRAS‐mutated cells in vitro . CD16 158V ‐CR T cells also effectively controlled subcutaneous growth of HCT116 cells in CB17‐SCID mice in vivo . Thus, CD16 158V ‐CR T cells combined with cetuximab represent useful reagents to develop innovative EGFR+KRAS‐mutated CRC immunotherapies. Abstract : What's new? KRAS mutations downstream the epidermal growth factor receptor (EGFR) represent the major limitation in monoclonal antibody‐targeted therapy of EGFR+ colorectal cancers. To restore the sensitivity of KRAS‐mutated cancer cells to EGFR‐specific mAbs, here the authors explore different strategies based on the generation of extracellular CD16‐chimeric receptors linked to intracellular signalling and subsequent transduction into T cells. They demonstrate that T cells engineered with CD16 158V ‐chimeric receptor can be redirected by EGFR‐specific mAbs toward EGFR+ cancer cells, overcoming the limitation conferred by KRAS mutations in vitro and in vivo . This study might help develop innovative and effective treatments of EGFR+ KRAS‐mutated cancers.